Perilaku mencontek siswa dan peran guru bimbingan dan konseling dalam penanganannya - Fitri, Rahma; Ahmad, Riska (Universitas Negeri Padang, 2023)
In following the learning process at school, a student does not always get good learning results, sometimes the results obtained are not in accordance with the expected results. In the implementation of the learning process, two student characters will appear, namely positive student characters who are actively involved in learning activities and negative student characters who are passive and commit fraudulent acts in learning activities such as cheating or imitating assignments and peer tests. Cheating is copying answers, trading in exam answers, viewing exams illegally, turning in someone else's work, soliciting other students' answers and changing record grades. This study aims to describe students' cheating behavior and the teacher's role in handling it. The population of this study included 974 students of SMA N 1 Ampek Angkek, the sample size was 252 people, obtained by random sampling technique. This research is a descriptive research with quantitative research methods. Data was collected by administering a questionnaire, and analyzed using percentages. The results of the study revealed: 1) The findings of the study regarding cheating behavior at SMA N 1 Ampek Angkek were generally in the moderate category with a frequency of 184 and a percentage of 73.02%. This means that more than half of the students who are the sample of the study still practice cheating behavior, either independently planned, individually opportunistic, socially active or socially passive. 2) The role of the counseling teacher in handling cheating behavior is provided with guidance and counseling services such as information services, educational services individual counseling, group counseling services, group counseling services and content mastery services.